2014
DOI: 10.1177/216507991406200304
|View full text |Cite
|
Sign up to set email alerts
|

Finnish Occupational Health Nurses' View of Work-Related Stress

Abstract: Occupational stress at work has been increasingly recognized as a major risk factor for chronic disease and poor quality of work life among employees. The purpose of this study was to examine how occupational health nurses in Finland manage work-related stress. A descriptive cross-sectional study design was used with a sample of 354 Finnish occupational nurses who responded to the survey. No specific standardized tools to assess or handle work-related stress in occupational health services or their client comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Not only would these individuals have to experience the mental stress and upheaval of their normalcy through losing their source of income, but they then encountered a greater level of workload in the new occupation they secured. Secondly, those who were not allowed to decide on the pace of their work are also more likely to work irregular hours such as at night, and were more likely to stress over their workload which was previously commonly seen with those who worked in the healthcare industry ( Kinnumen-Amoroso & Liira, 2014 ; Kang et al , 2015 ; Jin et al , 2019 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Not only would these individuals have to experience the mental stress and upheaval of their normalcy through losing their source of income, but they then encountered a greater level of workload in the new occupation they secured. Secondly, those who were not allowed to decide on the pace of their work are also more likely to work irregular hours such as at night, and were more likely to stress over their workload which was previously commonly seen with those who worked in the healthcare industry ( Kinnumen-Amoroso & Liira, 2014 ; Kang et al , 2015 ; Jin et al , 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, a recent study found that more than half of the US workforce felt burned out and 40% were considering changing jobs to resolve stress ( Talkspace, 2021 ). While the influence of occupational-related stress on the health of workers is increasingly being recognized ( Kinnunen-Amoroso and Liira, 2014 ; Bruschini et al , 2018 ; Jukic et al , 2020 ; Doyle et al , 2021 ), relatively little research has been conducted with a focus on how the ongoing pandemic has exacerbated these occurrences.…”
Section: Introductionmentioning
confidence: 99%
“…While the influence of occupational-related stress on the health of workers is increasingly being recognized [37][38][39][40][41][42], to date, relatively little research has been conducted with a focus on longitudinal salivary cortisol collection in conjunction with the documentation of daily stressor events. One study, by Eller et al (2006), used survey response answers to describe participants, i.e., age, smoking status, children, and work-related questions, to name a few, but the lack of a diary limited the ability to truly connect cortisol fluctuations with what the participant was exposed to at a given time, on a given day [43].…”
Section: Introductionmentioning
confidence: 99%